2022
DOI: 10.1093/plphys/kiac581
|View full text |Cite
|
Sign up to set email alerts
|

The Mediator complex subunit MED25 interacts with HDA9 and PIF4 to regulate thermomorphogenesis

Abstract: Thermomorphogenesis is, among other traits, characterised by enhanced hypocotyl elongation due to induction of auxin biosynthesis genes like YUCCA8 by transcription factors, most notably PHYTOCHROME INTERACTING FACTOR 4 (PIF4). Efficient binding of PIF4 to the YUCCA8 locus under warmth depends on HISTONE DEACETYLASE 9 (HDA9) activity, which mediates histone H2A.Z depletion at the YUCCA8 locus. However, HDA9 lacks intrinsic DNA binding capacity, and how HDA9 is recruited to YUCCA8, and possibly other PIF4-targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…Previous genetic analysis suggested that MED25 acts downstream of phyB (Cerdan & Chory, 2003). More recently, MED25 was identified to interact with PIF4 control hypocotyl elongation in tomato and Arabidopsis (Sun et al ., 2020; Shapulatov et al ., 2022). We performed in vitro pull‐down experiments using purified GST‐MED25 and MBP‐HDA19‐GFP and found that GST‐MED25 pulled down MBP‐HDA19‐GFP, but not MBP‐GFP (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous genetic analysis suggested that MED25 acts downstream of phyB (Cerdan & Chory, 2003). More recently, MED25 was identified to interact with PIF4 control hypocotyl elongation in tomato and Arabidopsis (Sun et al ., 2020; Shapulatov et al ., 2022). We performed in vitro pull‐down experiments using purified GST‐MED25 and MBP‐HDA19‐GFP and found that GST‐MED25 pulled down MBP‐HDA19‐GFP, but not MBP‐GFP (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HDA19 belongs to the RPD3‐like subclass and does not bind to DNA directly, but is instead recruited to chromatin as a member of transcriptional repressive complexes (Song et al ., 2005; Wang et al ., 2013; Jing et al ., 2021). We and others demonstrate that HDA19 is an essential negative regulator of photomorphogenesis, whereas HDA15 and HDA9 positively regulate skotomorphogenesis and thermomorphogenesis, respectively (Benhamed et al ., 2006; Liu et al ., 2013; Gu et al ., 2017; van der Woude et al ., 2019; Zhao et al ., 2019; Jing et al ., 2021; Shapulatov et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…An additional functional link between PIFs and HDACs are the subunits MED25 (MEDIATOR 25) and MED14 (MEDIATOR 14) of the Mediator complex (Bajracharya et al, 2022;Guo et al, 2023;Shapulatov et al, 2023), which is an evolutionary conserved large multi-subunit protein complex regulating RNAPII function on various levels (Allen and Taatjes, 2015;Soutourina, 2018). MED25 or PFT1 (PHYTOCHROME AND FLOWERING TIME 1) was first discovered as a SAS regulator and can interact with PIF4 in Arabidopsis and tomato to recruit RNAPII (Sun et al, 2020;Shapulatov et al, 2023). During TM, MED25 can associate with HDA9, thereby potentially facilitating the PIF4-mediated recruitment of HDA9 for histone deacetylation at the PIF4 and YUC8 gene (Figure 1) (Shapulatov et al, 2023).…”
Section: Histone Acetylation Dynamicsmentioning
confidence: 99%
“…MED25 or PFT1 (PHYTOCHROME AND FLOWERING TIME 1) was first discovered as a SAS regulator and can interact with PIF4 in Arabidopsis and tomato to recruit RNAPII (Sun et al, 2020;Shapulatov et al, 2023). During TM, MED25 can associate with HDA9, thereby potentially facilitating the PIF4-mediated recruitment of HDA9 for histone deacetylation at the PIF4 and YUC8 gene (Figure 1) (Shapulatov et al, 2023). Moreover, PIF1 and PIF3 also interact with MED25 and HDA19 to down-regulate the expression of positive the positive PM regulators BBX21 and GLK1 via histone deacetylation and reducing chromatin accessibility (Figure 1) (Guo et al, 2023).…”
Section: Histone Acetylation Dynamicsmentioning
confidence: 99%
“…This likely explains why the overexpression of GLK2 resembled the phenotypes of pif4-2 upon high temperature and/or exogenous auxin treatment (Figures 5.2 and 5.5). We also propose that the impeded thermomorphogenesis caused by GLK2 overexpression in this study might be due to feedback regulation of PIF4 as PIF4 can modulates its own expression by binding its own promoter (Lee et al, 2021b;Shapulatov et al, 2023). GLK2 thus may affect the expression of PIF4, downstream of PIF4, and acts as an autofeedback regulator to modulate thermomorphogenesis.…”
Section: Glk2 In Thermomorphogenesis Chaptermentioning
confidence: 71%